Pendampingan Teknis serta Diagnosa Kerusakan Pompa Sumur Bor di Gampong Luthu Lamweu, Kecamatan Sukamakmur, Kab. Aceh Besar, Provinsi Aceh - Zulfadhli, Zulfadhli; Husni, Husni; Sabri, Sabri (Universitas Syiah Kuala, 2024)
The aim of this Community Service (PKM) activity is to provide technical assistance and diagnose damage to drilled well pumps in Gampong Luthu Lamweu, Sukamakmur, Aceh Besar. This method of implementing community service begins with conducting a location survey, outreach to the community, students involved and prospective Thematic KKN students. Next, form a service team and explain the work program, work targets and implementation targets. From the results of field diagnosis and verification, it was found that the installation of the submersible pump was not in accordance with the technical specification data on the pump. This is what makes the pump that was installed in 2021 unable to work as it should after testing the pump (run test). The PKM team recommends: the size of the output pipe be increased from